2018
DOI: 10.1080/19396368.2018.1478470
|View full text |Cite
|
Sign up to set email alerts
|

Inhibin B in seminiferous tubules of human testes in normal spermatogenesis and in idiopathic infertility

Abstract: β-TGF: β-transforming growth factor family; GCA: germ cell abnormalities/atypia; JS: Johnsen score; FSH: follicle stimulating hormone; TESE: testicular sperm extraction; LH: luteinizing hormone; F-Testo: free testosterone; ELISA: the enzyme-linked immunosorbent assay; CV: coefficient of variance; DR: range of definitions; AZF: azoospermia factorI; HC: immunohistochemical; HIER: heat induction of epitope retrieval; H&E: hematoxylin and eosin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…Pulsatile release of gonadotropin-releasing hormone (GnRH) from the hypothalamus stimulates the release of FSH and LH. Inhibin B and estradiol are the primary inhibitors of FSH secretion (2123). Several other pituitary-regulatory proteins, such as activin and follistatin, have been implicated in FSH secretion and action (22).…”
Section: Introductionmentioning
confidence: 99%
“…Pulsatile release of gonadotropin-releasing hormone (GnRH) from the hypothalamus stimulates the release of FSH and LH. Inhibin B and estradiol are the primary inhibitors of FSH secretion (2123). Several other pituitary-regulatory proteins, such as activin and follistatin, have been implicated in FSH secretion and action (22).…”
Section: Introductionmentioning
confidence: 99%
“…The level of serum inhibin B is significantly correlated with testicular volume and total sperm count, which directly reflects testicular spermatogenic function and fertility 39 . One study found that the content of inhibin B in testicular convoluted seminiferous tubules in infertile people was significantly lower than that in control individuals 40 . The results of this study showed that the concentration of inhibin B in the nutrient medium of TM4 cells decreased after exposure to 2,4‐D in a dose‐dependent manner.…”
Section: Discussionmentioning
confidence: 57%
“…39 One study found that the content of inhibin B in testicular convoluted seminiferous tubules in infertile people was significantly lower than that in control individuals. 40 The results of this study showed that the concentration of inhibin B in the nutrient medium of TM4 cells decreased after exposure to 2,4-D in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 60%
“…The reduced level of testosterone and prolactin might be due to hyperglycemia that increased free radical production to induce oxidative stress, triggered testicular tissue, particularly Leydig cells, and reduced their function associated with reduced beta-cells function and increased insulin resistance [40,43,44]. In contrast, the decreased level of testosterone was the main reason for a high level of LH due to the feedback mechanism, whereas the high level of FSH might be due to dysfunction of Sertoli cells and seminiferous tubules that reduced inhibin secretion [45].…”
Section: Discussionmentioning
confidence: 99%